Diagnostic work up to assess early response indicators in invasive pulmonary aspergillosis in adult patients with haematologic malignancies - Heinz, Werner J.; Vehreschild, Jörg Janne; Buchheidt, Dieter (Mycoses, 2018)
In immunocompromised patients with acute leukaemia as well as in allogeneic hematopoietic stem cell transplant patients, pulmonary lesions are commonly seen. Existing guidelines provide useful algorithms for diagnostic procedures and treatment options, but they do not give recommendations on how to evaluate early success or failure and if or when it is best to change therapy. Here, we review the diagnostic techniques currently used in association with clinical findings and propose an approach using a combination of computer tomography, clinical and all available biomarkers and inflammation parameters, especially those positive at baseline, to assess early response in invasive pulmonary aspergillosis. Computed tomography scans should be carried out at regular intervals during early and long-term follow-up. Imaging on day seven, or even earlier in clinically unstable patients, combined with an additional testing of biomarkers and inflammatory markers in between, is needed for a reliable assessment at day 14. If no improvement is seen after 2 weeks of therapy or the clinical condition is deteriorating, a change of antifungal therapy should be considered. Alleged breakthrough infections or treatment failure should undergo early diagnostic workup, including tissue biopsies when possible, to retrieve fungal cultures for resistance testing.
First published: 17 October 2018
Gesehen am 23.09.2019